2004
DOI: 10.1177/0162243903259188
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Technological Culture: A Programmatic Proposal for a Pragmatist Approach

Abstract: Neither traditional philosophy nor current applied ethics seem able to cope adequately with the highly dynamic character of our modern technological culture. This is because they have insufficient insight into the moral significance of technological artifacts and systems. Here, much can be learned from recent science and technology studies (STS). They have opened up the black box of technological developments and have revealed the intimate intertwinement of technology and society in minute detail. However, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 29 publications
1
97
0
7
Order By: Relevance
“…Studies in other settings have reported similarly high consent rates for the use of residual tissue in medical research (Hamajima et al, 1998;Malone et al, 2002;Stegmayr and Asplund, 2002;Jack and Womack, 2003;Furness and Nicholson, 2004;Chen et al, 2005;Wheeler et al, 2007;Bryant et al, 2008). Our results show that patients prefer to be informed about research with tissue, refuting authors who argue that patients do not need to be informed and do not need to be provided with the opportunity to opt-out or withhold consent for future research with residual tissue (Keulartz et al, 2004;Swierstra, 2004). Respondents felt respected and valued by being informed, but most felt that actually giving consent was of secondary importance (66% did not prefer 'one-time consent'), as was also observed by Hamilton et al (2007) and previous studies of our own group (Vermeulen et al, 2009a, b).…”
Section: Discussionsupporting
confidence: 43%
“…Studies in other settings have reported similarly high consent rates for the use of residual tissue in medical research (Hamajima et al, 1998;Malone et al, 2002;Stegmayr and Asplund, 2002;Jack and Womack, 2003;Furness and Nicholson, 2004;Chen et al, 2005;Wheeler et al, 2007;Bryant et al, 2008). Our results show that patients prefer to be informed about research with tissue, refuting authors who argue that patients do not need to be informed and do not need to be provided with the opportunity to opt-out or withhold consent for future research with residual tissue (Keulartz et al, 2004;Swierstra, 2004). Respondents felt respected and valued by being informed, but most felt that actually giving consent was of secondary importance (66% did not prefer 'one-time consent'), as was also observed by Hamilton et al (2007) and previous studies of our own group (Vermeulen et al, 2009a, b).…”
Section: Discussionsupporting
confidence: 43%
“…Dies behaupten etwa pragmatistische autoren [10] oder Vertreter einer sog. "integrativen empirischen ethik" ([16-18, 25]; dazu auch: [19,20]).…”
Section: Zur Methodik Angewandter Ethikunclassified
“…Thus, science, technology and society are not separate entities but are fundamentally entangled. Furthermore, STS have shown that technological artifacts are not to be understood as neutral and passive instruments but rather as value-laden and active forces, as 'agents' that influence how we live, how we act, how we relate to each other, how we understand the world and our place in it, and what we aspire to, desire and hope for (Keulartz et al 2004;Verbeek 2005). To return to the bumper sticker: indeed, the gun may not shoot someone on its own, but its availability certainly does influence how the user thinks and acts.…”
Section: Co-evolution Of Science and Technology And Societymentioning
confidence: 99%